A STUDY ON THE TRADITIONAL AGRICULTURAL TOOLS AND SKILLS OF THE ANGAMI NAGAS - Rutsa, Vikeyienuo (International Journal of Research -GRANTHAALAYAH, 2024)
Since time immemorial, our forefathers have had the knowledge and skills to create and craft a variety of implements and tools to assist themselves in all the different work they did for survival. With their indigenous knowledge, they crafted different tools for different work at different seasons. Traditional agricultural tools were made up of locally available materials like bamboo, wood etc. Agriculture, being the primary and most important occupation of the Angami Naga, our forefathers grew and cultivated their own crops. From the richest to the poorest, all Angami folks owned their own plot of land and fields and maintain self-sufficiency. Survival was never a problem for them, which is why the need to import food from outside never arose, nor was there any worry about shortage of food. The ingenuity and innate intelligence to work efficiently and earn one’s livelihood is, thus, very clear. This study is undertaken to identify various traditional tools used for agricultural purposes by the farmers and also to explore the surviving skills of the Angami community. The research is conducted mostly in and around Kohima village which is considered as the second largest village in the Asian Continent. The fieldwork is documented through interviews and discussions. The study is descriptive in nature. It is intended that this paper may raise interest and inspire more in-depth research in the field.